Trace Element Geochemistry and Stable Isotopic (?13C and ?15N) Characterisation of Nevşehir Coals, Türkiye - Kara, Hatice; Kalender, Leyla; Yumutgan, Mehmet cagay (Mdpi, 2025)
The Nev & scedil;ehir coals are located in the Central Anatolian Crystalline Complex (CACC), T & uuml;rkiye, and no reports exist on trace element, nitrogen, and carbon isotope composition data of the Nev & scedil;ehir coals. The present study aims to geochemically characterise the Nev & scedil;ehir coals to determine their trace elemental enrichment patterns and possible sources. Nev & scedil;ehir coals are found within Late Miocene K & imath;z & imath;l & ouml;z Formation (Arafa Member) rocks. These coals are part of the huminite maceral group; the dominant maceral group is ulminites. The minerals in coals are inorganic, such as oxidised framboidal pyrite, iron oxide minerals, quartz, clay, and carbonate minerals. Coals have great potential regarding trace elements. Benefits might arise from mining and using some of the critical elements derived from coal. Compared with the world coal average, the coal samples in this study are enriched in As (149.25 mu g/g), V (245 mu g/g), Cr (159 mu g/g), Ga (18 mu g/g), Ni (216 mu g/g), Th (17 mu g/g), Zn (143 mu g/g), and U (54 mu g/g). The arsenic content in this study is associated with inorganic components such as oxidised framboidal pyrite. Vanadium in coal is mainly associated with aluminosilicates and organic matter. Chromium originates from the clay minerals within coals. Uranium in coal is mainly associated with organic matter. Nickel and zinc in coal are predominantly associated with sulphides. The delta 15N contents of the samples are comparable to those of several references, including plants, terrestrial creatures, and organic nitrogen. The delta 13C-delta 15N isotopic range and average values for four coal samples ranged from -25.66 parts per thousand to -25.91 parts per thousand (-25.80 parts per thousand) and 3.6 parts per thousand to 4.3 parts per thousand (3.9 parts per thousand), respectively, demonstrating that C3 type modern terrestrial vegetation was common in the palaeomires of the studied coal seams.
Keywords: coal; trace element; carbon isotope; nitrogen isotope